Foot-and-mouth disease (FMD) vaccination and control in cattle at the wildlife/livestock interface of the Mnisi communal area - Fosgate, Geoffrey Theodore (University of Pretoria, 2019)
Dissertation (MSc)--University of Pretoria, 2014.